Delirium in Acute Stroke: A Survey of Screening and Diagnostic Practice in Scotland. (12th August 2013) - Carin-Levy, Gail; Nicol, Kath; van Wijck, Frederike; Mead, Gillian E.
Abstract : Aims . To survey the use of delirium screening and diagnostic tools in patients with acute stroke across Scotland and to establish whether doctors and nurses felt the tools used were suitable for stroke patients. Methods . An invitation to participate in a web-based survey was e-mailed to 217 doctors and nurses working in acute stroke across Scotland. Descriptive statistics were used to report nominal data, and content analysis was used to interpret free text responses. Results . Sixty-five responses were logged (30% return rate). 48% of the respondents reported that they routinely screened newly admitted patients for delirium. Following initial screening, 38% reported that they screened for delirium as the need arises. 43% reported using clinical judgment to diagnose delirium, and 32% stated that they combined clinical judgment with a standardised tool. 28% of the clinicians reported that they used the Confusion Assessment Method; however, only 13.5% felt that it was suitable for stroke patients. Conclusions . Screening for delirium is inconsistent in Scottish stroke services, and there is uncertainty regarding the suitability of screening tools with stroke patients. As the importance of early identification of delirium on stroke outcomes is articulated in recent publications, validating a screening tool to detect delirium in acute stroke is recommended.